Using OSLO for the Optics teaching - Montalvo, R. A. (2012)
Oslo is a software allow to design optical systems in an interactive graphical environment using an optical elements set such as mirrors, lens, prisms, diafragms, pupils, showing the parameters details of each element which are added succesively to finally obtain the optical system with expected parameters we want to build. In this paper, we compare the theoretical models and OSLO results for the design of an achromatic len, an parallel plates prism and achromatic len with the Scheimpflug condition for validating purposes of the OSLO as a computer didactic tool for teaching geometric and paraxial optics.